Pomegranate‐Inspired Design of Highly Active and Durable Bifunctional Electrocatalysts for Rechargeable Metal–Air Batteries. (11th March 2016) - Li, Ge; Wang, Xiaolei; Fu, Jing; Li, Jingde; Park, Moon Gyu; Zhang, Yining; Lui, Gregory; Chen, Zhongwei
Abstract: Rational design of highly active and durable electrocatalysts for oxygen reactions is critical for rechargeable metal–air batteries. Herein, we report the design and development of composite electrocatalysts based on transition metal oxide nanocrystals embedded in a nitrogen‐doped, partially graphitized carbon framework. Benefiting from the unique pomegranate‐like architecture, the composite catalysts possess abundant active sites, strong synergetic coupling, enhanced electron transfer, and high efficiencies in the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). The Co3 O4 ‐based composite electrocatalyst exhibited a high half‐wave potential of 0.842 V for ORR, and a low overpotential of only 450 mV at the current density of 10 mA cm −2 for OER. A single‐cell zinc–air battery was also fabricated with superior durability, holding great promise in the practical implementation of rechargeable metal–air batteries.